(untitled) (Tabularium Historiae, 2020)
The author intended to reveal the significance of local patriotic women in maintaining the national identity of compatriots in Bydgoszcz just before Polish independence. Women’s patriotic activity in Bydgoszcz is shown in the background of women from Great Poland activities in Pozen District. Women from Bydgoszcz are shown as women engaged in work to sustain and create Polish identity in the German city just before and during World War I. This article is very important for Polish historiography because the history of Polish women patriots in Bydgoszcz is for the first time researched. Polish women activists, unknown for most people in Bydgoszcz and unexplored as a part of local history so far, will be added to the Pantheon of famous man-patriots. Recovery of historical memory of women from Bydgoszcz fight against Germanization from the 19/20 century to the end of 1918 was an important part of this project’s author purpose.